A Planar Gas Sensor Based on Mobility Spectrometry for Chemicals On-line Detection - Zhao*, Dongjie; Liu, Jun (Asian Journal of Chemistry, 2014)
With concern for chemical attacks from terrorism, there is an urgent need for a method which can continuously and accurately detect hazardous chemicals. In this study, a planar gas sensor based on mobility spectrometry was demonstrated, which can get spectra for chemical detection in one second. Corona discharge (CD) is used as the ionization source. Three kinds of hazardous chemicals are measured and spectra exhibits remarkably differences. This planar gas sensor based on mobility spectrometry is a promising method for trace hazardous chemicals detection.